VANET Security Framework for Trusted Grouping Using TPM Hardware - Wagan, A.A.; Mughal, B.M.; Hasbullah, H. (2010 Second International Conference on Communication Software and Networks, 2010)
Vehicular Ad hoc Network (VANET) is a network of vehicles on the roads, of which the success of its applications is highly dependent upon the underlying security mechanism. The default trial asymmetric PKI/ECDSA security mechanism is known for its high computational cost, thus lacking applicability in life-critical safety messaging. Alternative security schemes, such as symmetric methods provide faster communication at the expense of reduced security. Hence, hybrid and hardware based solutions were proposed by researchers to ease the issue. However, these solutions either do not support the existing VANET PKI standard or have larger message size. In this paper, we present a hardware based security framework that uses both standard asymmetric PKI and symmetric cryptography for faster and secure safety message exchange. The proposed framework is expected to improve security mechanism in VANET by developing trust relationship among the neighboring nodes, hence forming trusted groups. The trust is established via Trusted Platform Module (TPM) and group communication.